Mapping Household Adaptive Capacity to Climate Change through Sustainable Livelihood Assets in Coastal Urban Communities - Trida Ridho Fariz; Dwi Rahmawati; Abdul Jabbar; Andhina Putri Heriyanti; Putri Alifa Kholil; Amnan Haris; Rifa’ Atunnisa; Maulana Malik Wicaksono (Yayasan Keluarga Guru Mandiri, 2026)
Coastal communities are increasingly exposed to climate-related hazards. This study analyzes and maps household adaptive capacity in a coastal urban area in Semarang, using the Sustainable Livelihood Framework to examine how natural, human, physical, financial, and social capital shape resilience. A mixed-methods approach was applied through census-based household surveys, participatory mapping, in-depth interviews, spatial analysis, Spearman correlation to explore capital interlinkages, and AHP weighting to assess the relative importance of livelihood assets. The results reveal contrasting interaction patterns across neighborhood units: human–financial linkages dominate in RT 06/RW 01, while physical–natural interactions are strongest in RT 07/RW 05. AHP results indicate that social capital is the most influential asset, emphasizing the role of organizational participation and community networks. Most households fall into the Moderate adaptive capacity category. By translating household-level assessments into spatially explicit priorities, this study supports community empowerment through strengthened social networks, improved climate literacy, urban farming initiatives, and advocacy for secure land tenure. The findings provide a practical foundation for participatory coastal adaptation planning and offer a methodological reference for climate adaptation research oriented toward community empowerment in the Global South, particularly in Indonesia.